2009
DOI: 10.1177/000348940911800704
|View full text |Cite
|
Sign up to set email alerts
|

Dysplasia in Adults with Recurrent Respiratory Papillomatosis: Incidence and Risk Factors

Abstract: Dysplasia was discovered in more than 20% of adult patients with RRP studied over a 6-year period. Age, gender, tobacco history, and operative frequency were not identifiable risk factors for the presence of dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
34
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 11 publications
8
34
1
Order By: Relevance
“…We report a male preponderance among AoRRP patients, which is consistent with earlier published studies 17, 23. A similar sex disparity is well documented for oropharyngeal cancer 8, 24.…”
Section: Discussionsupporting
confidence: 92%
“…We report a male preponderance among AoRRP patients, which is consistent with earlier published studies 17, 23. A similar sex disparity is well documented for oropharyngeal cancer 8, 24.…”
Section: Discussionsupporting
confidence: 92%
“…Use of cidofovir requires the surgeon and patient to understand the medication's potential for adverse effects on renal function, hepatic function, hematopoiesis, and on the endolarynx. The toxicities of cidofovir, as well as its relationship to laryngeal mucosal dysplasia and neoplasia in the setting of RRP have been reviewed 12…”
Section: Resultsmentioning
confidence: 99%
“…It is challenging to compare our results with previous studies due to varying terminology and end-points. [54], [55] We applied a dual classification system, which separates low-and high-grade neoplasia, widely used in reporting histopathological findings in the anogenital tract. In a cohort of 129 patients with RRP, Sanchez et al [6] reported a total incidence of 13.2% for moderate and severe dysplasias, a figure not dissimilar from our own.…”
Section: Discussionmentioning
confidence: 99%